Relationships between trace elements and cognitive and depressive behaviors in sprague dawley and wistar albino rats - Yavuz, Melis; Dayanc, Ekin Dongel; Merve Antmen, Fatma; Keskinöz, Elif; Altuntaş, Esra; Dolu, Gökçen; Koç, Berkcan; Tunçcan, Emre; Şakar, Damla; Canözer, Ufuk; Büyüker, Ceyda; Polat, Ece; et al. (Frontiers in Pharmacology, 2024)
Introduction: This study investigates the effects of social isolation on mental health and cognitive functions in Sprague Dawley (SD) and Wistar Albino (WIS) rat strains, prompted by the heightened awareness of such impacts amid the COVID-19 pandemic. This study aims to explore the impact of social isolation on memory, learning, and behavioral changes in middle-aged SD and WIS rat strains and to investigate cortical trace element levels, seeking potential correlations between these levels and the observed behavioral responses to social isolation. Methods: Four groups of 14-month-old male rats were established: control and isolated SDs and WIS rats (CONT-SD, ISO-SD, CONT-WIS, ISO-WIS). Morris Water Maze and Porsolt Forced Swimming tests were conducted for behavioral assessment. Following behavioral tests, rats were sacrificed under general anesthesia, and cortices were isolated for analysis of macro and trace element levels (ICP/MS). Results: In behavioral tests, CONT-SD rats exhibited superior performance in the Morris Water Maze test compared to CONT-WIS rats, but displayed increased depressive behaviors following social isolation, as evident in the Porsolt Forced Swimming test (p < 0.05). ISO-SD rats showed elevated levels of Co and Cu, along with reduced levels of Cs and As, compared to ISO-WIS rats. Moreover, isolation resulted in decreased Cu and Mo levels but increased Rb levels in WIS rats. Comparison of trace element levels in naïve groups from different strains revealed lower Zn levels in the WIS group compared to SD rats. Discussion: The findings suggest that the SD strain learns faster, but is more susceptible to depression after isolation compared to the WIS strain. Increased Co and Cu levels in ISO-SD align with previous findings, indicating potential trace element involvement in stress responses. Understanding these mechanisms could pave the way for preventive treatment strategies or therapeutic targets against the consequences of stressors, contributing to research and measures promoting a balanced diet to mitigate neurobehavioral abnormalities associated with social isolation in the future.